The Impact of Climate Change on Fruit Production: Adaptive Mechanisms in Horticultural Crops: Subject Review - Obaid, Parwen Alaaldin (American Journal of Biodiversity, 2025)
This paper offers an extensive view of the impacts of climate change on fruit and horticulture and discusses how horticultural plants respond to a changing environment. The study starts by emphasizing the significance of fruit crops in food security and its economic role in the field of agriculture. It also examines natural changes to the climate, from the rising temperatures of the so-called “dust bowl” event and changing rainfall patterns to severe drought and atmospheric CO₂ levels. The work delves into negative effects of climate change on fruit, such as shifted flowering and ripening schedules, lowering of fruit quality, and escalating fruit-invading diseases and pests. It also addresses the physiological and anatomical mechanisms employed by plants for adaptation including the control of stomatal opening, modulation of photosynthesis, and root distribution with special reference to osmotic substance production for combating water and heat stress. The research also underscores the value of adaptive agriculture, including planting date adaptations, smart irrigation, and pruning and shading methods. It also *showcases the role of biotechnology and gene editing for example in developing varieties resistant to both to drought and heat using CRISPR technology. The study includes cases studies representing a variety of crops, such as grapes, olives, and citrus, and adaptation responses in different geographical regions. It also highlights challenges and future research directions, including long-term cross-scale studies, climate model accuracy, and international cooperation. Last, but not least, it highlights the importance to transfer scientific knowledge to agricultural side, to steer policies toward the sustainable agriculture, to strengthen investments in research and development for ensuring the sustainability and improvement of fruit production in climate change frame.